The purposes and problems of correction of convicts in the mechanism of ensuring penitentiary safety (Journal of actual problems of jurisprudence, 2018)
In article it is necessary to be able to distinguish the having features and the general signs of a task and the purpose of convicts. Tasks as the purposes are the last result of a certain stage of activity; as the purposes are considered in two forms, types – expected and as the result received in practice. Types of these tasks can be not corresponding, they depend not only on scientific providing, also organizational and the operating features of activity. In practice the task as the purpose improves according to contents and situations.Key words: Penitentiary safety, criminal and executive right, educational corrective labors, work, convicts, imprisonment.